A Novel Yeast Genus and Two Novel Species Isolated from Pineapple Leaves in Thailand: Savitreella phatthalungensis gen. nov., sp. nov. and Goffeauzyma siamensis sp. nov. - Pumin Nutaratat; Wanatchaporn Boontham; Pannida Khunnamwong (Journal of Fungi, 2022)
Four yeast strains, representing one genus and two novel anamorphic yeast species, were isolated from pineapple leaves collected in Thailand. Analysis of the sequences of the D1/D2 domains of the large subunit (LSU) rRNA gene and the internal transcribed spacer (ITS) regions showed the two strains (DMKU-PAL186 and DMKU-PAL178) were closely related to the type strains of the Protomyces and Taphrina species, but with high nucleotide divergence. Two strains (DMKU-PAL39 and DMKU-PAL18) were found to be closely related to the type strains of Goffeauzyma iberica, but with eight nucleotide substitutions in the D1/D2 domains and 26 nucleotide substitutions in the ITS regions. In phylogenetic analyses, the strains DMKU-PAL186 and DMKU-PAL178 formed a well-separated lineage from Protomyces and Taphrina genera, confirming that they represented a distinct genus, while the strains DMKU-PAL39 and DMKU-PAL18 represented a species in the genus Goffeauzyma, which was phylogenetically distinct from other recognized species of the genus. Based on molecular analyses and phenotypic characteristics, the names Savitreella gen. nov. (Taphrinomycetes, Ascomycota) and Savitreella phatthalungensis sp. nov. are proposed to accommodate the strains DMKU-PAL186 and DMKU-PAL178, and the name Goffeauzyma siamensis sp. nov. (Tremellomycetes, Basidiomycota) is proposed to accommodate the strains DMKU-PAL39 and DMKU-PAL18.